The role of international organizations in the protection and restoration of the cultural heritage of Ukraine in the conditions of armed aggression: Financial, economic and legal aspects - Tsugorka, Oleksandr; Byrkovych, Tetyana; Denysіyuk Zhanna; Kravchenko, Anastasiia; Boyko, Vyacheslav; Kotviakovskyi, Yurii (Edelweiss Applied Science and Technology, 2024)
The article attempts to analyze the role of international organizations in the protection and restoration of the cultural heritage during war conflicts. The case of Ukrainian ongoing conflict is considered, based on systematization of UNESCO documents and activities, as well as the case of Syria as a ‘testing ground’ for UNESCO in efforts on protection and restoration of cultural heritage damaged due to hostilities. It is claimed that UNESCO in fact showed its low efficiency in protecting cultural heritage, but is capable of providing reasonable steps of post-war restoration and preventing illegal trade of stolen cultural heritage. The expedience of developing international law grounds for protection of cultural heritage is emphasized, together with employing mechanisms of public-private partnership in restoration projects.